The Effect of Environmental Performance and Sustainability Reporting on Firm Value With Green Financing as Moderating Variable - eva aditya putri pratama; Dien Noviany Rahmatika; Abdulloh Mubarok (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2025)
This study aims to examine the effect of environmental performance and sustainability reporting on firm value with green financing as a moderating variable in mining companies listed on the IDX in 2020-2024, the data used in this study are secondary data in quantitative research. The population in the study was 89 companies, the sampling technique used purposive sampling which resulted in 22 sample companies x 5 years of research resulting in 110 observations. The data analysis method uses multiple linear analysis and moderation regression analysis. Individual test results show that environmental performance variables have a significant negative effect on firm value, sustainability reporting has no effect on firm value, green financing strengthens the effect of environmental performance on firm value and green financing does not moderate the effect of sustainability reporting on firm value. This finding highlights the importance of green financing in supporting environmental initiatives that impact firm valuation. Keywords: Environmental Performance, Sustainability Reporting, Green Financing, Firm Value